2018
DOI: 10.5812/ijp.64353
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Prevalence of Dental Enamel Defects and Other Oral Findings in Children with and Without Celiac Disease

Abstract: Background: Dental enamel defects and other oral manifestations are reported to occur more commonly in children with celiac disease (CD). Our aim was to investigate the frequency and distribution of enamel defects and dental caries, and the presence of other oral findings in children with CD and to compare them to a group of children without CD. Methods: From 200 index cases with CD, 65 cases aged between three to 16 years accepted to participated in the study after an oral explanation for the parents. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 23 publications
(29 reference statements)
2
19
0
2
Order By: Relevance
“…This comes in agreement with a study by Shahraki et al when studying wider range of sample age (3-16 years) and larger sample size (65) of CD patients. (14) Structural abnormalities were also present at lesser extent as Aine's II was in 10% of the sample which contained no Ain's III or IV and this comes in an agreement with a Turkish study that reported no Aine's III or IV in 60 CD patients' ages 6-16 years. (21) The present study revealed that the least intestinal damage (Marsh II) came with no CD specific DED while the more intestinal damage (Marsh III-a and III-b) came with more CD specific DED and this comes in contrast with what Aine et al showed by studying adults enamel defects in relation to the degree of histological damage although children cannot be compared to adults.…”
Section: Discusionsupporting
confidence: 85%
See 2 more Smart Citations
“…This comes in agreement with a study by Shahraki et al when studying wider range of sample age (3-16 years) and larger sample size (65) of CD patients. (14) Structural abnormalities were also present at lesser extent as Aine's II was in 10% of the sample which contained no Ain's III or IV and this comes in an agreement with a Turkish study that reported no Aine's III or IV in 60 CD patients' ages 6-16 years. (21) The present study revealed that the least intestinal damage (Marsh II) came with no CD specific DED while the more intestinal damage (Marsh III-a and III-b) came with more CD specific DED and this comes in contrast with what Aine et al showed by studying adults enamel defects in relation to the degree of histological damage although children cannot be compared to adults.…”
Section: Discusionsupporting
confidence: 85%
“…Early diagnosis of CD patients by dentists can be performed by DED since most CD patients are atypical. (14,20) In the present study almost half of the sample had no CD specific enamel defects, however, most of the defects were enamel opacities (Aine's I). This comes in agreement with a study by Shahraki et al when studying wider range of sample age (3-16 years) and larger sample size (65) of CD patients.…”
Section: Discusionmentioning
confidence: 41%
See 1 more Smart Citation
“…6,8 Increased risk of dental caries is suggested to be associated with CD. While this statement is supported by the results of certain studies 24,39 other authors report opposing findings. Dental decay is a common disorder in children and is multifactorial in aetiology, so it might not be a particularly useful means of identifying CD, although retrospectively, it can be noted.…”
Section: Discussionmentioning
confidence: 90%
“…Providing the prevalence rate of MIH could be extracted, studies with a primary outcome rather than prevalence of MIH in random population were also included. Only one study was excluded because of small sample size [ 17 ]. Fifteen studies met the final inclusion criteria for the review [ 18 – 32 ].…”
Section: Resultsmentioning
confidence: 99%